Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.15557/jou.2019.0014
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of peritoneal tuberculosis

Abstract: PurposeThe objective of this work was to describe different presentations of peritoneal tuberculosis on ultrasound.Materials and methodsThis was a retrospective study conducted between 2008 and 2016 at the Main Hospital in Dakar, and including 38 cases of peritoneal tuberculosis. The tests were performed on Philips Envisor and Hitachi Preirus with 10 and 12 MHz linear transducers. The mean age was 26 years and the sex ratio was 0.8. The diagnosis of peritoneal tuberculosis was based on histological evidence (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…3 Before this, a handful of Senegalese purchased the less effective pegylated interferon abroad or in downtown Dakar, at the country's best-stocked private pharmacy. HEPADAK subjects were enrolled by specialists in four Dakar hospitals and private clinics (Vray et al, 2006), who were referred as HBV infected individuals by major blood banks. Confronted with difficulties in using biopsy to assess liver damage, project researchers negotiated additional funding to purchase and evaluate a trademarked liver ultrasonograph, a portable and noninvasive imaging technology, in Dakar (Mbaye et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…3 Before this, a handful of Senegalese purchased the less effective pegylated interferon abroad or in downtown Dakar, at the country's best-stocked private pharmacy. HEPADAK subjects were enrolled by specialists in four Dakar hospitals and private clinics (Vray et al, 2006), who were referred as HBV infected individuals by major blood banks. Confronted with difficulties in using biopsy to assess liver damage, project researchers negotiated additional funding to purchase and evaluate a trademarked liver ultrasonograph, a portable and noninvasive imaging technology, in Dakar (Mbaye et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Its incidence remains considerable in endemic areas. It represents 5–10 % of all locations and 50–58 % of abdominal locations [ 4 ]. This form affects young adults between 20 and 40 years of age [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It ranks fourth after pulmonary, lymph node and osteoarticular tuberculosis, and is characterized by clinical and paraclinical diversity [ 3 ]. The incidence of peritoneal tuberculosis was estimated to be 50–58 % of abdominal locations [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Second, abdominal ultrasonography is useful in evaluating the therapeutic effects of the treatment of intestinal tuberculosis and tuberculous peritonitis. One study found that the abdominal ultrasonographic findings of 38 cases of tuberculous peritonitis revealed the involvement of the parietal peritoneum in 89.4%, ascites in 84.2%, anomalies of the greater omentum in 73.6%, and mesentery abnormalities in 63.1% of the patients [ 11 ]. In this case, all of these findings were confirmed at the onset of treatment and were consistent with the clinical diagnosis of tuberculous peritonitis.…”
Section: Discussionmentioning
confidence: 99%